The Influence of Word of Mouth And Taste on Purchasing Decisions at Mie Balap AMI - Rezeki, Sri; Manik, Desma Erica Maryati; Tannaldy, Jaccyn (Dinasti Publisher, 2025)
This study aims to analyze the influence of Word of Mouth (WOM) and taste on consumer purchasing decisions at Mie Balap Ami, a culinary business located in Pasar Metal, Medan. The background of this study is based on the fluctuations in income that occurred throughout 2024, where the highest income was recorded in April and the lowest in September. The decline is thought to be influenced by weak WOM and inconsistency in product taste. This study uses a quantitative approach with multiple linear regression analysis techniques. Data were collected through questionnaires from 100 respondents selected using non-probability sampling techniques. Validity and reliability tests were carried out to ensure the reliability of the instrument, as well as classical assumption tests to ensure the feasibility of the model. The results of the study show that: (1) Word of Mouth has a significant effect on purchasing decisions; (2) Taste has a significant effect on purchasing decisions; and (3) Word of Mouth and taste simultaneously have a significant effect on consumer purchasing decisions at Mie Balap Ami. These findings indicate that the strength of WOM and consistency of taste are key factors in maintaining and increasing consumer loyalty in the culinary industry.